View Single Post
Old 2020-02-23, 20:17   #2
R.D. Silverman
 
R.D. Silverman's Avatar
 
Nov 2003

723210 Posts
Default

Quote:
Originally Posted by wildrabbitt View Post
Hi,

the following is something I've been reading.





He started from the power series



\(\sum_{n=1}^\infty \big(\frac{n}{q}\big)x^n=\frac{1}{1-x^q}\sum_{m=1}^{q-1}\big(\frac{m}{q}\big)x^m=\frac{xf(x)}{1-x^q}\)


say, and by putting this in the formula


\(\Gamma(s)n^{-1}=\int_0^1 x^{n-1}(\log x^{-1})^{s-1} \mathrm{d}x\)


he obtained


\(\Gamma(s)L(s)=-\int_0^1\frac{f(x)}{x^q-1}(\log x^{-1})^{s-1}\mathrm{d}x\)


I'm stuck because I can't see how he put what he put in the formula.


Can anyone explain it step by step?
I am getting "math processing error". Your post is not being parsed correctly.
R.D. Silverman is offline   Reply With Quote